Average Error: 0.0 → 0.0
Time: 10.2s
Precision: 64
$\left(\sinh x - 1\right) \cdot \frac{1}{2}$
$\left(\sinh x - 1\right) \cdot \frac{1}{2}$
\left(\sinh x - 1\right) \cdot \frac{1}{2}
\left(\sinh x - 1\right) \cdot \frac{1}{2}
double f(double x) {
double r35928049 = x;
double r35928050 = sinh(r35928049);
double r35928051 = 1.0;
double r35928052 = r35928050 - r35928051;
double r35928053 = 2.0;
double r35928054 = r35928051 / r35928053;
double r35928055 = r35928052 * r35928054;
return r35928055;
}


double f(double x) {
double r35928056 = x;
double r35928057 = sinh(r35928056);
double r35928058 = 1.0;
double r35928059 = r35928057 - r35928058;
double r35928060 = 2.0;
double r35928061 = r35928058 / r35928060;
double r35928062 = r35928059 * r35928061;
return r35928062;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\left(\sinh x - 1\right) \cdot \frac{1}{2}$
2. Final simplification0.0

$\leadsto \left(\sinh x - 1\right) \cdot \frac{1}{2}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "(sinh(x)-1)*(1/2)"
(* (- (sinh x) 1.0) (/ 1.0 2.0)))